2023
DOI: 10.3389/fneur.2023.1124886
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Compound heterozygous NUP85 variants cause autosomal recessive primary microcephaly

Abstract: Nucleoporin (NUP) 85 is a member of the Y-complex of nuclear pore complex (NPC) that is key for nucleocytoplasmic transport function, regulation of mitosis, transcription, and chromatin organization. Mutations in various nucleoporin genes have been linked to several human diseases. Among them, NUP85 was linked to childhood-onset steroid-resistant nephrotic syndrome (SRNS) in four affected individuals with intellectual disability but no microcephaly. Recently, we broaden the phenotype spectrum of NUP85-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Delays in nuclear pore complex insertion and envelope closure were seen with SMPD4 knockdown (Smits et al ., 2023). Nuclear pore formation defects and variants in nuclear pore proteins are known to cause microcephaly (Carapito et al, 2019; Fujita et al, 2018; Ravindran et al, 2021; Ravindran et al, 2023; Rosti et al, 2017; Sandestig et al, 2020). Nucleoporin proteins localize to the base of the primary cilium in addition to the nuclear envelope (Kee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Delays in nuclear pore complex insertion and envelope closure were seen with SMPD4 knockdown (Smits et al ., 2023). Nuclear pore formation defects and variants in nuclear pore proteins are known to cause microcephaly (Carapito et al, 2019; Fujita et al, 2018; Ravindran et al, 2021; Ravindran et al, 2023; Rosti et al, 2017; Sandestig et al, 2020). Nucleoporin proteins localize to the base of the primary cilium in addition to the nuclear envelope (Kee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, brain MRI abnormalities included delayed myelination, complete agenesis and/or hypoplasia of the corpus callosum, grey matter heterotopia, cortical malformation of the left frontal lobe, the absence of the cingulate gyrus, and simplified gyration of the cerebral cortex (refer to Table 1 for additional clinical details). These results can be largely explained by functional studies that revealed how the kind of mutation, such as hypomorphic and/or loss of function, led to variable severity phenotypes [29]. Specifically, missense variants affecting conserve residues of NUP85 impaired the protein function and its interaction with substrates, with distinct and organ-specific consequences [18,29].…”
Section: Discussionmentioning
confidence: 99%
“…These results can be largely explained by functional studies that revealed how the kind of mutation, such as hypomorphic and/or loss of function, led to variable severity phenotypes [29]. Specifically, missense variants affecting conserve residues of NUP85 impaired the protein function and its interaction with substrates, with distinct and organ-specific consequences [18,29]. Missense mutations p.Ala581Pro and p.Arg645Trp and splice site mutation c.405+1G>A of NUP85 were reported to prevent the interaction between NUP85 protein and its binding partner NUP160 and were associated with SRNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in constituents of NUP107-160 complex have also been correlated to several developmental disorders. In this context, biallelic mutations in NUP85 (Table 2) have been linked to microcephaly (MCPH) and Seckel syndrome spectrum disorders (MCPH-SCKS; [96,97]). MCPH-SCKS includes a inhomogeneous group of diseases characterised by primary microcephaly with otherwise normal brain appearance and other variable findings including cognitive impairment, short stature, and abnormal facial features (facial dysmorphism) [98].…”
Section: Developmental Disorders: Microcephalymentioning
confidence: 99%